Gamification Application for Promoting and Encouraging Physical Activity in the Elderly - Narmin Mohammed Noori; Awaz Naaman Saleem; Muhammed Anwar (Eurasian Journal of Science and Engineering)
Physical activity positively promotes calmness and lowers stress levels, overall quality of life, and subjective well-being, particularly among older people. Isolation, shifts in cognition, and a decline in motor abilities are some of the negative consequences of ageing that make many seniors wary of exercise programs. In mobile technology, notably gamification applications, game design features can spark older people's intrinsic motivation, encouraging them to participate in and enjoy physical activity. Despite a growing body of research on this topic, there is still a lack of consensus regarding the nature and extent of older adults' knowledge and healthcare professionals about gamification applications and physical health outcomes among this demographic group. This study seeks to address this gap by examining healthcare professionals' perspectives on using gamification applications to rehabilitate patients' physical activities and overall well-being. Specifically, the study explores the needs, motivations, and obstacles healthcare workers face concerning this approach. qualitative description method was followed to understand the fundamental perspectives of healthcare professionals, capture the experiences of patients and professionals to ensure reliable and trustworthy results and contribute to the credibility and validity of the study. Interviews were reviewed several times, and to analyze, content analysis was used, furthermore, texts were imported into MAXQDA software version 10, which supported the content analysis. The results showed that gamification applications can give patients a sense of support and community while also assisting patients in improving the management of their chronic diseases. Gamification applications can improve the efficiency and convenience of physical exercise programs. However, when an application crashes or is infected with a virus, it can provide patients with false information, exposing users to attacks from hackers when they are using it. Incorrect diagnosis poses a risk to a patient's life as risks and ethical considerations due to using gamification applications in physical activity.